2010
DOI: 10.1016/j.ajhg.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Uncommon Recurrent Potocki-Lupski Syndrome-Associated Duplications and the Distribution of Rearrangement Types and Mechanisms in PTLS

Abstract: Nonallelic homologous recombination (NAHR) can mediate recurrent rearrangements in the human genome and cause genomic disorders. Smith-Magenis syndrome (SMS) and Potocki-Lupski syndrome (PTLS) are genomic disorders associated with a 3.7 Mb deletion and its reciprocal duplication in 17p11.2, respectively. In addition to these common recurrent rearrangements, an uncommon recurrent 5 Mb SMS-associated deletion has been identified. However, its reciprocal duplication predicted by the NAHR mechanism had not been id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 54 publications
3
126
0
2
Order By: Relevance
“…Após estudos 4,6,7 , evidências mostram que o gene dosagem-sensível denominado RAI1 seja o possível responsável pelas variações fenotípicas que conferem ao portador da SPL características autísticas, assim como as demais características 4,6,7 . Tal abordagem parece justificar a variabilidade clí- relato de caso nica adversa presente neste caso clínico quando comparado às constatações realizadas pela literatura científica 1,2,[5][6][7] até o presente momento.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Após estudos 4,6,7 , evidências mostram que o gene dosagem-sensível denominado RAI1 seja o possível responsável pelas variações fenotípicas que conferem ao portador da SPL características autísticas, assim como as demais características 4,6,7 . Tal abordagem parece justificar a variabilidade clí- relato de caso nica adversa presente neste caso clínico quando comparado às constatações realizadas pela literatura científica 1,2,[5][6][7] até o presente momento.…”
Section: Discussionunclassified
“…relato de caso INTRODUÇÃO A Síndrome de Potocki-Lupski (SPL), que recebeu essa denominação por ter sido descrita pela primeira vez em abril de 2007 pelos autores Lorraine Potocki e James Lupski, consiste em alteração genética caracterizada pela duplicação na região 17p11.2, associada com a duplicação 17p11.2p11.2 1,2 . A duplicação corresponde à repetição de um segmento de um braço cromossômico, podendo o segmento duplicado terminar em uma posição diferente no mesmo cromossomo ou em um cromossomo diferente 3 .…”
unclassified
“…For example, although the majority of SMS/PTLS patients present with either deletion or duplication of the same ~3.7 Mb genedense region, there is significant variability in the clinical phenotype [112]. Furthermore, while there are some significant differences in the incidence of the abnormalities in patients with the common deletion/duplication compared to those patients with smaller or larger-sized CNVs, a clear distinction between these sub-groups of patients cannot be made; many of these phenotypes are therefore likely strongly influenced by genetic background as well as environmental effects [83,94]. While gene-environment interactions may potentially explain the source of the variability seen in these syndromes, investigation into the specific environmental factors that may affect outcomes for these genomic disorders has yet to be undertaken.…”
Section: Gene-environment Interactionsmentioning
confidence: 95%
“…This duplicated segment contains 14 genes, including both RAI1, the major contributing gene for the reciprocal deletion causing SMS, as well as the steroid-metabolism regulating gene, SREBP1. This patient demonstrates all typical PTLS phenotypes [94]. Whether, or to what extent, PTLS results from RAI1 gene over-dosage still remains to be elucidated, although mouse studies (described below) have shown that it is likely responsible for at least some of the symptoms [95].…”
Section: Smith-magenis and Potocki-lupski Syndromesmentioning
confidence: 99%
See 1 more Smart Citation